Transient In-Situ Identification of Thermal Parameters in Commercial Thermoelectric Modules using Transfer-Function Models - Pauzi, Gurum Ahmad; Alfiansyah, Irfan; Riyanto, Agus; Apriyanto, Donni Kis; Yulianti, Yanti; Warsito, Warsito (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2025)
Thermoelectric devices operate based on the Seebeck and Peltier effects and offer advantages such as high reliability, compact size, lightweight structure, and precise temperature control, making them attractive for electronics, automotive, and aerospace applications. However, accurate in-situ characterization of commercial thermoelectric modules remains challenging due to the limitations of conventional methods, which are often destructive, complex, or costly. This study proposes a novel, non-destructive, and cost-effective transient identification method based on the analysis of thermal response under electrical excitation. The system dynamics were modelled using first- and second-order transfer functions derived from energy conservation principles, enabling parameter estimation from transient temperature data. The proposed approach estimated thermal conductivity (0.747 and 1.129 W/m·K), Seebeck coefficient (35.57 and 21.35 K/A), thermal resistance (3.16 and 1.62 K/W), and thermal capacitance (1.17 and 4.36 J/K). The results demonstrate that the transfer-function-based model effectively captures the thermal dynamics of commercial modules and provides reliable parameter identification. This study contributes a practical in-situ characterization framework that can support thermoelectric performance evaluation and optimization of thermal system design for real-world applications